Ekranisasi Novel Asih Karya Risa Saraswati - Maldawati, Komang (Humanis; Vol 25 No 3 (2021), 2021)
This article discusses the story of Asih or Kasih. Asih is a ghost in the Novel of Asih was written by Risa Saraswati. She was chosen as an object of research based on several reasons such as the public’s response, both oral and written on social media. The characteristic of Risa Saraswati when she wrote this novel, The film of "Asih" was the fifth highest grossing film in Indonesia in 2018. Nurgiyantoro’s theory is used and the elevation of Eneste. The structure theory of Nurgiyantoro explains the plot, setting and the characterization. Eneste’s theory verifies the alterations in the novel Asih to the film such as increment, decrement and variation. A qualitative method is used with the reading technique, observe and note. The data was analyzed using descriptive analysis and cooperative methods by describing and comparing the results of the data that was found. This study was explained the alteration of plot, decrement and the alteration of variation.